Cation vacancies and electrical compensation in Sb-doped thin-film SnO2 and ZnO. (19th January 2015) - Korhonen, E; Prozheeva, V; Tuomisto, F; Bierwagen, O; Speck, J S; White, M E; Galazka, Z; Liu, H; Izyumskaya, N; Avrutin, V; Özgür, Ü; Morkoç, H
Abstract: We present positron annihilation results on Sb-doped SnO2 and ZnO thin films. The vacancy types and the effect of vacancies on the electrical properties of these intrinsically n -type transparent semiconducting oxides are studied. We find that in both materials low and moderate Sb-doping leads to formation of vacancy clusters of variable sizes. However, at high doping levels cation vacancy defects dominate the positron annihilation signal. These defects, when at sufficient concentrations, can efficiently compensate the n -type doping produced by Sb. This is the case in ZnO, but in SnO2 the concentrations appear too low to cause significant compensation.